Agreement strategy in youth conversations: functions and expression - Galinskaitė, Reda (Lietuvių kalba, 2011)
Applying the method of conversation analysis, the article investigates the functions and expression of the strategy of agreement in friendly conversations of Lithuanian youngsters. The analysis is based on one boys’ conversation (duration – 1 hour and 50 minutes), one girls’ conversation (2 hours and 2 minutes) and two mixed-type conversations (2 hours). Their total duration is 5 hours and 52 minutes.The analysis has demonstrated that one can perform the following functions in conversations by means of agreement: a) to support, justify the speaker; b) to defend and intercede the speaker or to let one’s interlocutor defend him/herself; c) to mock at a person who is not participating in the conversation; d) to support the interlocutor’s idea.The strategies of agreement depend on the type of conversation: in the conversations among boys and in mixed conversations it is common to mock at persons who are not participating in the conversation; in the case of conversations among girls the strategy is usually employed when one wants to support the interlocutor’s idea.Agreement in Lithuanian youth conversations may be expressed in the following ways: a) by brief utterances showing reaction; b) by repeating the speaker’s utterance; c) by finishing the speaker’s utterance; d) by an example; e) by a compliment.The expression of the strategies of agreement is also related to the type of conversation: in boys’ conversation it is most likely to express agreement by such phrases as ne, tai taip ("yeah, of course so"); ne, tai jo ("yeah, certainly") and the like; in same-sex conversations both boys and girls tend to strengthen the agreement by such words as aišku ("of course"), būtent ("exactly"), iš tikrųjų ("indeed") etc; in girls’ dialogues agreement is often expressed by finishing the interlocutor’s utterance or providing an example; in very rare cases in girls’ conversation agreement is expressed by a compliment.